Brood cycles in queenless colonies of Apis mellifera capensis - Crous, Kendall Lauren (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2010)
In a honeybee colony, the loss of a queen is considered to be a serious occurrence and, if a new queen is not produced, ultimately doomed. However, in colonies of Apis mellifera capensis (Cape honeybees), numerous pathways are available for a colony which unexpectedly losses a queen. At the onset of this experiment, four colonies of A. m. capensis were dequeened. Following this photographs of all brood frames in each colony were taken and the contents of the cells analysed. Cells were chosen at random but once selected were repeatedly analysed for the duration of the experiment. The contents of a total of 44 888 individual cells were analysed. Any queen cells constructed during the sampling period were removed, maintaining a queenless state. In each colony, as predicted, the removal of the queen evoked a variety of responses in an attempt to rectify the sudden loss. However, ultimately three of the four colonies absconded, leaving little by way of stores. Three of the four colonies initially attempted to rear a new queen while one colony was immediately invaded by a presumed foreign queen and hence any attempt at queen cell construction ceased. An increased number of queen cells in the swarm position were recorded in all colonies. The invasion of a colony by a foreign queen was considered to be a new pathway available for queenless colonies of A.m capensis. Worker policing and suspected brood cannibalism was prevalent in all sampled colonies yet in addition, the transfer of eggs and larvae from cell to cell was also observed which may have increased the suspected cases of policing and cannibalism. It was unclear whether an egg or larva had been consumed or simply moved to another cell on the brood frame. All colonies contained eggs from laying workers to varying degrees, based on the length of each individual sampling period which varied between colonies due to differences in absconding dates. A steady breakdown in the effectiveness of the division of labour amongst the worker bees was observed in each of the colonies highlighting the vital role of a queen. This breakdown was clearly seen in the reduction in general housekeeping within a colony. An increase in stores indicated a possible increase in the number of forager bees, thereby reducing the number of worker bees available for other duties. Pathways available to broodright colonies and strategies used following sudden queen loss are discussed.
Keywords: Cape honeybee; Bee culture -- Queen rearing; Bees -- Breeding